IMPROVEMENT OF ALBENDAZOLE DISSOLUTION BY DISPERSION METHOD IN SBA-15 BASE MESOPOROUS SILICA - Mahanani Dhilasari, Estu
Background: Albendazole is an anthelmintic benzimidazole derivatives that widely used in the therapy. This drug has a low solubility and slow dissolution rate. The amount of drug that could be absorbed in gastrointestinal tract depend on its dissolution rate. Dispersion of drug in the mesoporous silica is one of the alternative method that can be use to increase the solubility and dissolution rate of subtances. The purpose of this research was to increase the disssolution rate of albendazole using SBA-15 base mesoporous silica. Methods. SBA-15 mesoporous silica was constructed using Pluronic 123 and tetraetiloftosilica (TEOS). Then albendazole was dissolved in methanol or methanol-acid and loaded into mesoporous by stirring or solvent evaporation method. Characterization and evaluation of albendazole mesoporous was performed using infrared spectrophotometer (Fourierhransform-lnfra Red), XRay diffraction (Powder X-Ray Diffraction), and scanning electron microscopy (SEM). The surface area and volume of the pore of mesoporous was determined using nitrogen absorption method. The dissolution test of albendazole from mesoporous was conducted in the media of HCI 0, I N. Result: The maximum concentration of albendazole entrapped in mesoporous found from stirring method was 28 percent by using of mehanol-acid solvent. While from solvent evaporation method all of the drug can be fully recovered as a mixture of recrystallized albendaloze and albendazole entrapped in SBA-15 mesoporous. The PXRD result showed that the entrapment of albendazole in SBA-15 reduced its crystalinity degree, while FTIR analysis showed that there were no chemical interactions occured between albendazole with SBA-15 mesoporous. The free surface area and volume of SBA-15 mesoporous pores was decreased after entrapment of albendazole. The dissolution rate of albendazole from mesoporous was increased 4,4 times than pure albendazole. Conclusion: Preparation of albendazole dispersion in the SBA-15 mesoporous silica can improve its dissolution rate significantly.